5.1.29 Problems 2801 to 2900

Table 5.57: First order ode

#

ODE

Mathematica

Maple

5716

\[ {}\left (x^{2}+1\right ) y^{\prime }+y = \arctan \left (x \right ) \]

5717

\[ {}\left (-x^{2}+1\right ) z^{\prime }-x z = a x z^{2} \]

5718

\[ {}3 z^{2} z^{\prime }-a z^{3} = 1+x \]

5719

\[ {}z^{\prime }+2 x z = 2 a \,x^{3} z^{3} \]

5720

\[ {}z^{\prime }+z \cos \left (x \right ) = z^{n} \sin \left (2 x \right ) \]

5721

\[ {}x y^{\prime }+y = y^{2} \ln \left (x \right ) \]

5722

\[ {}x^{3}+3 x y^{2}+\left (y^{3}+3 x^{2} y\right ) y^{\prime } = 0 \]

5723

\[ {}1+\frac {y^{2}}{x^{2}}-\frac {2 y y^{\prime }}{x} = 0 \]

5724

\[ {}\frac {3 x}{y^{3}}+\left (\frac {1}{y^{2}}-\frac {3 x^{2}}{y^{4}}\right ) y^{\prime } = 0 \]

5725

\[ {}x +y y^{\prime }+\frac {x y^{\prime }}{x^{2}+y^{2}}-\frac {y}{x^{2}+y^{2}} = 0 \]

5726

\[ {}1+{\mathrm e}^{\frac {x}{y}}+{\mathrm e}^{\frac {x}{y}} \left (1-\frac {x}{y}\right ) y^{\prime } = 0 \]

5727

\[ {}{\mathrm e}^{x} \left (x^{2}+y^{2}+2 x \right )+2 y \,{\mathrm e}^{x} y^{\prime } = 0 \]

5728

\[ {}n \cos \left (n x +m y\right )-m \sin \left (m x +n y\right )+\left (m \cos \left (n x +m y\right )-n \sin \left (m x +n y\right )\right ) y^{\prime } = 0 \]

5729

\[ {}\frac {x}{\sqrt {1+x^{2}+y^{2}}}+\frac {y y^{\prime }}{\sqrt {1+x^{2}+y^{2}}}+\frac {y}{x^{2}+y^{2}}-\frac {x y^{\prime }}{x^{2}+y^{2}} = 0 \]

5730

\[ {}\frac {x^{n} y^{\prime }}{b y^{2}-c \,x^{2 a}}-\frac {a y x^{a -1}}{b y^{2}-c \,x^{2 a}}+x^{a -1} = 0 \]

5731

\[ {}2 x y+\left (y^{2}-2 x^{2}\right ) y^{\prime } = 0 \]

5732

\[ {}\frac {1}{x}+\frac {y^{\prime }}{y}+\frac {2}{y}-\frac {2 y^{\prime }}{x} = 0 \]

5733

\[ {}x y^{\prime }-y = \sqrt {x^{2}+y^{2}} \]

5734

\[ {}8 y+10 x +\left (5 y+7 x \right ) y^{\prime } = 0 \]

5735

\[ {}x^{2}+2 x y-y^{2}+\left (y^{2}+2 x y-x^{2}\right ) y^{\prime } = 0 \]

5736

\[ {}y^{2}+\left (x y+x^{2}\right ) y^{\prime } = 0 \]

5737

\[ {}\left (x \cos \left (\frac {y}{x}\right )+y \sin \left (\frac {y}{x}\right )\right ) y+\left (x \cos \left (\frac {y}{x}\right )-y \sin \left (\frac {y}{x}\right )\right ) x y^{\prime } = 0 \]

5738

\[ {}\left (x^{2} y^{2}+x y\right ) y+\left (x^{2} y^{2}-1\right ) x y^{\prime } = 0 \]

5739

\[ {}\left (x^{3} y^{3}+x^{2} y^{2}+x y+1\right ) y+\left (x^{3} y^{3}-x^{2} y^{2}-x y+1\right ) x y^{\prime } = 0 \]

5740

\[ {}x^{2}+y^{2}+2 x +2 y y^{\prime } = 0 \]

5741

\[ {}x^{2}+y^{2}-2 x y y^{\prime } = 0 \]

5742

\[ {}2 x y+\left (y^{2}-3 x^{2}\right ) y^{\prime } = 0 \]

5743

\[ {}y+\left (-x +2 y\right ) y^{\prime } = 0 \]

5744

\[ {}x y^{\prime }-a y+y^{2} = x^{-2 a} \]

5745

\[ {}x y^{\prime }-a y+y^{2} = x^{-\frac {2 a}{3}} \]

5746

\[ {}u^{\prime }+u^{2} = \frac {c}{x^{{4}/{3}}} \]

5747

\[ {}u^{\prime }+b u^{2} = \frac {c}{x^{4}} \]

5748

\[ {}u^{\prime }-u^{2} = \frac {2}{x^{{8}/{3}}} \]

5749

\[ {}\frac {\sqrt {f \,x^{4}+c \,x^{3}+c \,x^{2}+b x +a}\, y^{\prime }}{\sqrt {a +b y+c y^{2}+c y^{3}+f y^{4}}} = -1 \]

5750

\[ {}{y^{\prime }}^{2}-5 y^{\prime }+6 = 0 \]

5751

\[ {}{y^{\prime }}^{2}-\frac {a^{2}}{x^{2}} = 0 \]

5752

\[ {}{y^{\prime }}^{2} = \frac {1-x}{x} \]

5753

\[ {}{y^{\prime }}^{2}+\frac {2 x y^{\prime }}{y}-1 = 0 \]

5754

\[ {}y = a y^{\prime }+b {y^{\prime }}^{2} \]

5755

\[ {}x = a y^{\prime }+b {y^{\prime }}^{2} \]

5756

\[ {}y = \sqrt {1+{y^{\prime }}^{2}}+a y^{\prime } \]

5757

\[ {}x = \sqrt {1+{y^{\prime }}^{2}}+a y^{\prime } \]

5758

\[ {}y^{\prime }-\frac {\sqrt {1+{y^{\prime }}^{2}}}{x} = 0 \]

5759

\[ {}x^{2} \left (1+{y^{\prime }}^{2}\right )^{3}-a^{2} = 0 \]

5760

\[ {}1+{y^{\prime }}^{2} = \frac {\left (x +a \right )^{2}}{2 a x +x^{2}} \]

5761

\[ {}y = x y^{\prime }+y^{\prime }-{y^{\prime }}^{2} \]

5762

\[ {}y = x y^{\prime }+\sqrt {b^{2}-a^{2} {y^{\prime }}^{2}} \]

5763

\[ {}y = x y^{\prime }+x \sqrt {1+{y^{\prime }}^{2}} \]

5764

\[ {}y = x y^{\prime }+a x \sqrt {1+{y^{\prime }}^{2}} \]

5765

\[ {}x -y y^{\prime } = a {y^{\prime }}^{2} \]

5766

\[ {}y y^{\prime }+x = a \sqrt {1+{y^{\prime }}^{2}} \]

5767

\[ {}y y^{\prime } = x +y^{2}-y^{2} {y^{\prime }}^{2} \]

5768

\[ {}y-\frac {1}{\sqrt {1+{y^{\prime }}^{2}}} = x +\frac {y^{\prime }}{\sqrt {1+{y^{\prime }}^{2}}} \]

5769

\[ {}y-2 x y^{\prime } = x {y^{\prime }}^{2} \]

5770

\[ {}\frac {-x y^{\prime }+y}{y^{2}+y^{\prime }} = \frac {-x y^{\prime }+y}{1+x^{2} y^{\prime }} \]

5771

\[ {}2 x y+\left (x^{2}+y^{2}\right ) y^{\prime } = 0 \]

5772

\[ {}\left (x +\sqrt {y^{2}-x y}\right ) y^{\prime }-y = 0 \]

5773

\[ {}x +y-\left (x -y\right ) y^{\prime } = 0 \]

5774

\[ {}x y^{\prime }-y-\sin \left (\frac {y}{x}\right ) x = 0 \]

5775

\[ {}2 x^{2} y+y^{3}+\left (x y^{2}-2 x^{3}\right ) y^{\prime } = 0 \]

5776

\[ {}y^{2}+\left (x \sqrt {y^{2}-x^{2}}-x y\right ) y^{\prime } = 0 \]

5777

\[ {}\frac {y \cos \left (\frac {y}{x}\right )}{x}-\left (\frac {x \sin \left (\frac {y}{x}\right )}{y}+\cos \left (\frac {y}{x}\right )\right ) y^{\prime } = 0 \]

5778

\[ {}y+x \ln \left (\frac {y}{x}\right ) y^{\prime }-2 x y^{\prime } = 0 \]

5779

\[ {}2 y \,{\mathrm e}^{\frac {x}{y}}+\left (y-2 x \,{\mathrm e}^{\frac {x}{y}}\right ) y^{\prime } = 0 \]

5780

\[ {}x \,{\mathrm e}^{\frac {y}{x}}-y \sin \left (\frac {y}{x}\right )+x \sin \left (\frac {y}{x}\right ) y^{\prime } = 0 \]

5781

\[ {}x^{2}+y^{2} = 2 x y y^{\prime } \]

5782

\[ {}x \,{\mathrm e}^{\frac {y}{x}}+y = x y^{\prime } \]

5783

\[ {}y^{\prime }-\frac {y}{x}+\csc \left (\frac {y}{x}\right ) = 0 \]

5784

\[ {}x y-y^{2}-x^{2} y^{\prime } = 0 \]

5785

\[ {}x +2 y-4-\left (2 x -4 y\right ) y^{\prime } = 0 \]

5786

\[ {}3 x +2 y+1-\left (3 x +2 y-1\right ) y^{\prime } = 0 \]

5787

\[ {}x +y+1+\left (2 x +2 y+2\right ) y^{\prime } = 0 \]

5788

\[ {}x +y-1+\left (2 x +2 y-3\right ) y^{\prime } = 0 \]

5789

\[ {}x +y-1-\left (-y+x -1\right ) y^{\prime } = 0 \]

5790

\[ {}x +y+\left (2 x +2 y-1\right ) y^{\prime } = 0 \]

5791

\[ {}7 y-3+\left (2 x +1\right ) y^{\prime } = 0 \]

5792

\[ {}x +2 y+\left (3 x +6 y+3\right ) y^{\prime } = 0 \]

5793

\[ {}x +2 y+\left (y-1\right ) y^{\prime } = 0 \]

5794

\[ {}3 x -2 y+4-\left (2 x +7 y-1\right ) y^{\prime } = 0 \]

5795

\[ {}x +y+\left (3 x +3 y-4\right ) y^{\prime } = 0 \]

5796

\[ {}3 x +2 y+3-\left (x +2 y-1\right ) y^{\prime } = 0 \]

5797

\[ {}y+7+\left (2 x +y+3\right ) y^{\prime } = 0 \]

5798

\[ {}x +y+2-\left (x -y-4\right ) y^{\prime } = 0 \]

5799

\[ {}3 x^{2} y+8 x y^{2}+\left (x^{3}+8 x^{2} y+12 y^{2}\right ) y^{\prime } = 0 \]

5800

\[ {}\frac {2 x y+1}{y}+\frac {\left (y-x \right ) y^{\prime }}{y^{2}} = 0 \]

5801

\[ {}2 x y+\left (x^{2}+y^{2}\right ) y^{\prime } = 0 \]

5802

\[ {}{\mathrm e}^{x} \sin \left (y\right )+{\mathrm e}^{-y}-\left (x \,{\mathrm e}^{-y}-{\mathrm e}^{x} \cos \left (y\right )\right ) y^{\prime } = 0 \]

5803

\[ {}\cos \left (y\right )-\left (x \sin \left (y\right )-y^{2}\right ) y^{\prime } = 0 \]

5804

\[ {}x -2 x y+{\mathrm e}^{y}+\left (y-x^{2}+x \,{\mathrm e}^{y}\right ) y^{\prime } = 0 \]

5805

\[ {}x^{2}-x +y^{2}-\left ({\mathrm e}^{y}-2 x y\right ) y^{\prime } = 0 \]

5806

\[ {}2 x +y \cos \left (x \right )+\left (2 y+\sin \left (x \right )-\sin \left (y\right )\right ) y^{\prime } = 0 \]

5807

\[ {}x \sqrt {x^{2}+y^{2}}-\frac {x^{2} y y^{\prime }}{y-\sqrt {x^{2}+y^{2}}} = 0 \]

5808

\[ {}4 x^{3}-\sin \left (x \right )+y^{3}-\left (y^{2}+1-3 x y^{2}\right ) y^{\prime } = 0 \]

5809

\[ {}{\mathrm e}^{x} \left (y^{3}+x y^{3}+1\right )+3 y^{2} \left (x \,{\mathrm e}^{x}-6\right ) y^{\prime } = 0 \]

5810

\[ {}\sin \left (x \right ) \cos \left (y\right )+\cos \left (x \right ) \sin \left (y\right ) y^{\prime } = 0 \]

5811

\[ {}y^{2} {\mathrm e}^{x y^{2}}+4 x^{3}+\left (2 x y \,{\mathrm e}^{x y^{2}}-3 y^{2}\right ) y^{\prime } = 0 \]

5812

\[ {}y^{2}+y-x y^{\prime } = 0 \]

5813

\[ {}y \sec \left (x \right )+\sin \left (x \right ) y^{\prime } = 0 \]

5814

\[ {}{\mathrm e}^{x}-\sin \left (y\right )+\cos \left (y\right ) y^{\prime } = 0 \]

5815

\[ {}x y+\left (x^{2}+1\right ) y^{\prime } = 0 \]